Koncepcja ma??e?stwa z perspektywy prawa rzymskiego i kanonicznego. Niemodna instrucja? - Sitek, Bronis?aw (Rodzina w prawie, 2013)
The concept of marriage from the perspective of Roman law and canon law. An outdated institution?